Unraveling Post-Election Dynamics: An Analysis of Groupthink in the Wake of the 2023 Presidential Election - Insights from Atiku and Obi Supporters - Oladele, Kayode; Remilekun Fausat Sarumi (Universitas Medan Area, 2023)
A heated contention arose over the outcome of the 2023 presidential election in Nigeria, with fervent followers of Peter Obi and Atiku Abubakar staunchly asserting their positions. This research delves into the repercussions of post-election groupthink syndrome on the perceptions and perspectives of these politically charged groups. Spanning from February 25, 2023, to September 25, 2023, the study meticulously scrutinizes media sources to explore the factors contributing to the emergence and endurance of Groupthink within these factions. The findings illuminate the roles of echo chambers, charismatic leadership, and confirmation bias in shaping group dynamics, perpetuating entrenched beliefs. The implications of these revelations underscore the need for initiatives in media literacy and critical thinking to empower citizens to navigate the information landscape successfully. Political leaders are urged to prioritize inclusive, fact-based decision-making to counteract the adverse effects of Groupthink, fostering a more enlightened and harmonious political discourse in Nigeria.